Magneto-optical characterization of ZnO / Ni nano-laminate obtained via Atomic Layer Deposition. Issue 1 (February 2021) - Buchkov, K; Galluzzi, A; Blagoev, B; Paskaleva, A; Terziyska, P; Stanchev, T; Mehandzhiev, V; Tzvetkov, P; Kovacheva, D; Avramova, I; Nazarova, E; Polichetti, M
Abstract: The magneto-optical (MO) properties of ZnO / Ni transition metal oxide (TMO) nano-laminate structures prepared by Atomic Layer Deposition (ALD) have been investigated. The structural (XRD) and chemical composition (XPS) analysis confirm the ZnO formation and corresponding effect of Ni incorporation in the crystal lattice. The XPS identification of Ni I 2+ state, reveals also some minor traces of Ni(OH)2 inclusions. By using a MO Kerr effect microscopy, we have studied the local magnetic coercivity and its distribution and mapping of the ZnO/Ni nano-laminate sample on a microscale level. The statistical dispersion of the measured Hc values ranges between 100 and 400 Oe (peak value of ∼ 200 Oe) with minor inhomogeneity inclusions.